The Taxonomy of Indonesian Criminal Offense in Proving the Corporate Criminal Liability - et al., Erni Mustikasari (International Journal of Advanced Science and Technology, 2019)
The development of technology, business models, and the varied income streams which are influenced by the human behaviour changes and the dynamics of social processes have created a diversification of new types of crimes that committed by corporations which called by corporate crime. The attention to the importance of criminal responsibility for corporate crime appeared because this type of crime was capable of causing greater damage than the individual crimes with conventional crime typologies. Moreover, unlike the individual crimes, not all of the corporate crimes can be easily criminalized. Criminal liability is more difficult to prove when the motives and intentions of a crime cannot be attributed to the corporation even though the harm caused are very broad. This article aims to provide recommendations to the taxonomy model of Indonesia’s corporate criminal liability. The classification process is chosen as a method to generalize corporate actions that can be imposed by the corporation. This classification uses data analysis techniques that use abstraction and legal interpretation in qualitative normative research. The results of this study are expected to be able to assist in the preparation of taxonomy models of criminal acts so that all corporate criminal cases brought by the Public Prosecutor to the Court will have a proper basis that can be criminally responsible in accordance with corporate characteristics.